2022
DOI: 10.1017/s0007114522000034
|View full text |Cite
|
Sign up to set email alerts
|

Daily consumption of wild olive (acebuche) oil reduces blood pressure and ameliorates endothelial dysfunction and vascular remodelling in rats with NG-nitro-L-arginine methyl ester-induced hypertension

Abstract: Purpose: Despite numerous reports on the beneficial effects of olive oil in the cardiovascular context, very little is known about the olive tree’s wild counterpart (Olea europaea, L. var. sylvestris), commonly known as acebuche (ACE) in Spain. The aim of this study was to analyse the possible beneficial effects of an extra virgin ACE oil on vascular function in a rodent model of arterial hypertension induced by L-NAME (NG-nitro-L-arginine methyl ester). Methods: Four experimental groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Indeed, previous studies in our group revealed the ability of ACE oil to prevent vascular remodeling and restore systemic vascular function in L-NAME-treated rats. [33] The better outcomes observed in this regard in favor of ACE oil could be partly explained by differences in minor compounds with vasoactive properties, such as triterpene acids (e.g., oleanolic and maslinic acid). [34,35] Additional studies in hypertensive patients have highlighted the presence of arterial sclerosis and vascular contraction due to enhanced intravascular pressure in the choroid [36] and reduced retinal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies in our group revealed the ability of ACE oil to prevent vascular remodeling and restore systemic vascular function in L-NAME-treated rats. [33] The better outcomes observed in this regard in favor of ACE oil could be partly explained by differences in minor compounds with vasoactive properties, such as triterpene acids (e.g., oleanolic and maslinic acid). [34,35] Additional studies in hypertensive patients have highlighted the presence of arterial sclerosis and vascular contraction due to enhanced intravascular pressure in the choroid [36] and reduced retinal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on the anti-hypertensive effects of extra virgin OO are also supported by a range of animal models. Recent studies using extra virgin OO (20%) or wild OO (15%) dietary supplementation for 12 weeks demonstrated a reduction in both systolic and diastolic BP in hypertensive rats [ 38 , 39 ]. This hypotensive effect of OO might be exerted, at least in part, in an endothelium-dependent manner via improving NO bioavailability.…”
Section: The Effect Of Olive Oil On Cardiovascular Health and Diseasesmentioning
confidence: 99%
“…This hypotensive effect of OO might be exerted, at least in part, in an endothelium-dependent manner via improving NO bioavailability. Moreover, an OO-enriched diet alleviates vascular dysfunction, improves vascular remodeling and reduces aortic fibrosis in hypertensive rats [ 39 ]. Improvement of endothelial function after administration of OO can be attributed to the inhibition and/or scavenging of reactive oxygen species (ROS) [ 40 ].…”
Section: The Effect Of Olive Oil On Cardiovascular Health and Diseasesmentioning
confidence: 99%
“…Most of the research on the health attributes of a MDP over the last half century has focussed on cardiometabolic health and in particular CVD and type 2 diabetes mellitus. The prospective cohort evidence for the MDP effect on incident disease or CVD outcomes (9) is convincing (6) . A 2020 review included thirty-eight cohorts and three RCT (10) .…”
Section: The Evidence For the Role Of A Mdp In Cardiometabolic Healthmentioning
confidence: 99%
“…The health benefits of olive oil have been studied independently from the MDP. In a rodent model of arterial hypertension, extra virgin olive oil demonstrated vasodilator, antihypertensive, antioxidant as well as antifibrotic and hypertrophic properties (28) .…”
Section: A Mdp Inflammation and Other Chronic Conditionsmentioning
confidence: 99%